A 3D Numerical Method for Studying Vortex Formation Behind a Moving Plate (Communications in Computational Physics, 2018)
In this paper, we introduce a three-dimensional numerical method for computingthe wake behind a flat plate advancing perpendicular to the flow. Our numericalmethod is inspired by the panel method of J. Katz and A. Plotkin [J. Katz andA. Plotkin, Low-speed Aerodynamics, 2001] and the 2D vortex blob method of Krasny[R. Krasny, Lectures in Appl. Math., 28 (1991), pp. 385–402]. The accuracy of themethod will be demonstrated by comparing the 3D computation at the center sectionof a very high aspect ratio plate with the corresponding two-dimensional computation.Furthermore, we compare the numerical results obtained by our 3D numericalmethod with the corresponding experimental results obtained recently by Ringuette[M. J. Ringuette, Ph.D. Thesis, 2004] in the towing tank. Our numerical results areshown to be in excellent agreement with the experimental results up to the so-calledformation time.